MAIN CAUSES OF VAGINAL DISCHARGE (CIPEEX, 2025)
Complaints of vaginal discharge are common in primary care settings. Symptoms such as discharge with or without odor, dysuria, itching, or vulvar/vaginal burning are part of a scenario experienced by women of reproductive age. A thorough medical history reporting on the woman's health status, coupled with an effective physical examination with genital evaluation and collection of a sample of the discharge, are essential for establishing an accurate diagnosis and appropriate management. Based on this, the objective is to understand the main etiologies related to vaginal discharge. This study is an expanded summary based on searches in the PubMed, SciELO, Science Direct, and Lilacs databases, using the descriptors "Etiology," "Dysbiosis," "Sexually Transmitted Infections," "Vulvovaginitis," and their respective English equivalents. Thirteen articles published in the last five years and available in full were included, and 45 articles that did not meet the study objective were excluded. Vaginosis and vulvovaginitis with discharge occur when there is a change in the vaginal microbiota, either due to the introduction of a pathogenic microorganism or changes in the vaginal environment that favor microbial proliferation. Early diagnosis of these conditions is crucial to avoid potential negative impacts on the patient's health. Most diagnoses of vulvovaginitis include bacterial vaginosis, vulvovaginal candidiasis, trichomoniasis, and cytolytic vaginosis. Finally, it is important to demonstrate the importance of identifying the possible causes of vaginal discharge in order to propose appropriate therapeutic management and promote women's health and well-being.
Keywords: Vaginal discharge; Women's health; Etiology